Chemical composition of commercial tambaqui (Colossoma macropomum) cuts in different body weight classes (Amazon: Brazil) (Research, Society and Development, 2021)
It is important to know the nutritional composition of the fish, especially the nutritional value of the commercial cuts most consumed by the population. The aimed of this study was to evaluate the chemical composition of commercial tambaqui (Colossoma macropomum) cuts in different classes of body weight. The sample collections were carried out in processing units in two municipalities in the state of Rondônia, Brazil.  The Data on 200 fish were recorded, with weight ranging from 1000 to 4700 g. Five classes of body weight were established, class 1 - below 1.2 kg; class 2 - from 1.21 to 1.8 kg; class 3 - from 1.81 to 2.4 kg; class 4 - from 2.41 to 3.5 kg; class 5 - over 3.5kg. The commercial cuts were lyophilized and intended for chemical analysis. The Kruskal-Wallis test (α=0.05) was used to compare the averages. The composition of commercial cuts was different in weight classes (p